Competitive elite golf: A review of the relationships between playing results, technique and physique - Hellström, J. (Sports Medicine, 2009)
Elite golfers commonly use fitness and technical training to become more competitive. The aim of this paper was to review the literature regarding the relationships between elite golfers' playing results, technique and physique. The competitive outcome is a direct function of the score. The three golf statistical measures that show the strongest correlations to scoring average are greens in regulation (GIR), scrambling, and putts per GIR. However, more detailed game statistics are needed where the distances to the targets are known before and after the strokes.